PENGARUH KEPEMIMPINAN DAN PENGAWASAN TERHADAP DISIPLIN KERJA SECURITY PT. KARYA SATRIA ABADI PEKANBARU - Febri Setiyani; Machasin '; Dewita Suryati Ningsih (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to determine the effect caused by the variable leadership and supervision of the work discipline variable.In this study, the authors took a sample of 85 respondents. The method of analysis used in this study is the method of multiple regression analysis, partial regression, simultaneous test, the coefficient of determination, validity and reliability, and the classic assumption test (test for normality, heteroscedasticity test, and test Multicollinearity). With SPSS version 17.0.From the results of testing that has been done, t test results in partial leadership significant effect on employee work discipline PT. Karya Satria Abadi Pekanbaru, while partial supervision significant effect on labor discipline. F test results obtained from the F table value of 3.11 with a probability value (sig) = 0.00. Because the sig <0.05 then the decision is accepted Ha. Results of statistical test calculations show that the calculation results of statistical tests showed Ha accepted and Ho rejected. This means that leadership and supervision together (simultaneous) effect on employee work discipline PT. Karya Satria Abadi Pekanbaru. Based on the obtained test determination coefficient R square value of 0.398 means that R2 is approach to 1. This means that the greater the ability of the independent variable (X) describes the change in the dependent variable (Y) or in other words the variables affecting leadership and supervision of the work discipline of 39.8% while the remaining 60.8% is influenced by other variables not examined in this research.Keywords: Leadership, Supervision, and Work Discipline.